Book Review - Muhammed Haron (Journal for the Study of Religion, 2020)
Detailed studies on early ‘Cape’ Muslim personalities have not been easy to come by since only a few scholars/researchers succeeded to examine their lives. During the decades of the 20th century, most scholars who studied these early ‘Cape’ figures that hailed from the Melayu archipelago, wrote short exploratory essays. Examples are Prof Adrianus van Selms’ bibliographical entry of Shaykh Yusuf Al-Makassari’s (1626-1699) and Prof Gerrie Lubbe’s journal article on Imam Abdullah ibn Qadi ‘Abdus Salam (aka Tuan Guru [1712-1807]). These scholars covered snippets of these personalities’ lives that included brief background notes and other biographical information.